Sign Language Tutorial Book for Elementary School Science Terminology on the Topic of Human Growth and Development (BUTOIJO) - Luh Komang Ayu Irmayanti; Putu Nanci Riastini; Luh Sri Surya Wisma Jayanti (Universitas Pendidikan Ganesha, 2025)
The main problem in elementary science learning is the limited availability of learning resources that bridge communication between teachers, deaf students, and non-deaf students, particularly in understanding science terminology that is difficult to explain through conventional sign language. This condition reduces accessibility and the participation of deaf students in the learning process. This study aims to develop and examine the feasibility and practicality of a digital tutorial book based on local sign language for elementary science learning. The research employs a Research and Development (R&D) approach using the ADDIE model, which includes analysis, design, development, limited implementation, and evaluation stages. The subjects of the study consisted of teachers and students as product users. Data were collected through validation questionnaires from media, material, and language experts, as well as response questionnaires from teachers and students. Data analysis was conducted using descriptive quantitative techniques to assess the validity and practicality of the product. The results show that the validation scores from media, material, and language experts each reached 1.00, indicating a very high validity category. The practicality test showed that the teacher response percentage was 93.89% and the student response percentage was 95.28%, categorized as very practical. Therefore, the developed product is considered feasible and practical for use in inclusive learning. The implication of this study indicates that integrating local sign language into digital media can improve learning accessibility while supporting the preservation of sign language within the educational context.